PROSPEK PELEMBAGAAN HUKUM ISLAM DI INDONESIA - SAM, Achmad Al-Muhajir (LPPM IAI IBRAHIMY GENTENG BANYUWANGI, 2019)
Indonesian is constitutionally as the state of Pancasila and not as a religious state, but the state is able to accommodate a number of religious norms in the formation of legislation. Indonesia, as the largest Muslim country in the world with a diversity of ethnic, religious and ethnic groups, has chosen the plural of legal system. This situation provides an opportunity to source a specific law affects the formation and preparation of the norms of national law. Islamic law has long been used in the community, even before the colonial period, has significant effect in certain customary law in society. This paper describes the existence of Islamic Law in the plurality of national law amidst the process of the tug of political struggle of national law in reform era. This discussion is focused on the following; first, the prospect legal institution of Islamic law in Indonesia; second, the resistance and constraint in course of legal institution of Islamic law in Indonesia. This paper was as a result of library research using legal normative status, historical, and sociological point of view.